Prevalência e fatores associados à autoavaliação do estado de saúde entre adultos remanescentes de quilombos e comparação com população rural da Bahia: estudo de base populacional em comunidades quilombolas no nordeste do Brasil - Clavdia Nicolaena Kochergin (2014)
This study aimed to characterize the maroon population of Vitória da Conquista / BA according to the global health indicator, self-assessment of health status, identifying the prevalence of poor self-assessed health, and associated factors in Maroon population compared with the rural population of Bahia. A cross-sectional population-based study with 797 adult residents was conducted in individuals remaining Quilombos communities in Vitória da Conquista/ Bahia in 2011. Multivariate analyzes were performed by ordinal logistic regression, adjusted for sex and age. The prevalence of negative self-assessment (poor / very poor) was 12.5% and self-assessed health was associated with socioeconomic dimensions, demographic, lifestyle, social support and health status. Self-assessment of health status, presence of chronic disease, presence of limitation in usual activities because of health problems in the last 15 days: To compare the maroon population of Vitória da Conquista and the rural population of Bahia, the following outcomes were analyzed and limitations for performance of activities for self-care: toileting, feeding and bathing. Data on the rural population of Bahia were extracted from the National Sample Survey of Households conducted in 2008 (PNAD 2008). The differences between the proportions of the distribution of characteristics were tested with the chi-square distribution and calculated the percentage changes of differences in the prevalence of the four above-mentioned outcomes. In maroon population self-assessment of health status negative (fair, poor and very poor) your health 49.2% more; indicated 110.8% more than the presence of disease; 137.0% more limitation in daily activities due to health problems and 112.1% more difficult for self-care. Thus demonstrating that the maroon population is even more disadvantageous position in the rural population of Bahia. The Stata, version 12.0 was used for data analysis.